2016
DOI: 10.1002/gps.4516
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study on clinical correlates of anxiety disorders in 613 community living older adults in Hong Kong

Abstract: Older adults with anxiety disorders appeared to have greater medical comorbidity and lower cognitive function. While anxiety may affect memory performance, future studies are needed to explore if anxiety symptom may reflect early neurodegeneration that easily escapes clinical attention. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…To our knowledge, this is the first prospective study that provided a well‐matched comparison based on age, gender, and education to a large group of anxious older adults without dementia. We have previously reported a cross‐sectional linkage in anxiety and cognitive impairment in non‐demented older adults . At 3 years, we found that baseline anxiety symptoms were associated with poor performance in delayed recall and TMT at follow‐up.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…To our knowledge, this is the first prospective study that provided a well‐matched comparison based on age, gender, and education to a large group of anxious older adults without dementia. We have previously reported a cross‐sectional linkage in anxiety and cognitive impairment in non‐demented older adults . At 3 years, we found that baseline anxiety symptoms were associated with poor performance in delayed recall and TMT at follow‐up.…”
Section: Discussionmentioning
confidence: 77%
“…The baseline study was conducted from 2011 and 2013. These individuals were selected from a larger pool of 613 community‐dwelling older adults . They were matched with another 122 participants without anxiety symptoms at baseline based on age, gender, and education in the same pool.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxiety disorders in the elderly appear to be more likely associated with common medical conditions than those found in the general population [7]. Comorbid anxiety can complicate a patient’s medical treatment and outcome.…”
Section: Introductionmentioning
confidence: 99%